La securitizacion de la crisi colombiana: bases conceptuales y tendencias generales. - Arlene B. Tickner. (Colombia Internacional, 2004)
This article argues that perceptions of insecurity and threat produced by Colombia in neighboring countries are not the result of the objective consequences of the regionalization of the Colombian crisis, but rather, depend largely upon internal political dynamics in each country and the ways in which their representatives articulate specific issues as security problems. Following a general conceptual discussion of security and securitization, the author explores the primary practices of securitization that have been employed by Brazil, Colombia, Ecuador, Panama, Peru and Venezuela. This examination allows the article to conclude that the Colombian crisis and U.S. military policy in the region are two factors that currently determine the security dynamics in this zone.